Understanding collegiate esports : a practitioner's guide to developing community and competition - Hoffman, Jennifer Lee; Pauketat, Regena; Varzeas, Kelsey A. (New York, NY : Routledge, 2022)
"As esports is one of the new and rapidly growing sports programs at the collegiate level, today's campus leaders are increasingly asked to navigate the complexity of esports. This practical volume helps higher education professionals understand the expanding role of collegiate esports, describing the ecosystem of college esports and the experience for college players, as well as the connections between gaming and career preparation. Chapter authors offer an overview and practical look at the main structures and issues facing collegiate esports programs, athletes, and administrators, and addresses the needs of the campus gaming community, building gender and racial inclusivity, athlete health, amateurism and the esports athlete, the role of the technology industry, governance, career paths, and coaching. This cutting-edge volume offers information to support campus leaders and practitioners in building and expanding collegiate esports programs in the quickly growing and changing aspects of both online and face-to-face campus communities"--
Foreword / Karen Weaver, Ed.D -- Preface / Jennifer Lee Hoffman, Regena Pauketat, & Kelsey Varzeas -- Video games go to college / Jennifer Lee Hoffman & Tricia Seifert -- Shifting the narrative : using esports to amplify historically black colleges & universities / Wayne L. Black & Kishonna L. Gray -- "It's just part of the game" : confronting toxicity in esports and building inclusive Environments / Regena Pauketat -- Mental health and wellness for the esports student athlete / Kelsey A. Varzeas -- Coaching in esports : promoting well-being & performance / Yeonhee Cho, Eric S. Cohen, Autumn E. Freund, Jason Yip, & Jin Ha Lee -- (E)sports medicine on campus / Lindsey Migliore -- Organizing and governing collegiate esports / David Welch Suggs. Jr. -- Community, career, & competition : the University of Washington and the future of esports program building / Justin Camputaro, Trevor Whiton, Jason Hansen, & Adam Serafin -- Establishing a conference esports program and related legal issues for collegiate esports / Carolayne Henry.
Keywords: eSports (Contests) -- United States -- Management; College sports -- United States; EDUCATION / Higher; SPORTS & RECREATION / General